Flashback Characteristics of Kerosene Spray in Cross Flow under High Temperature and High Pressure. Issue 5 (4th April 2022) - Zhao, Yongsheng; Tian, Xiaohu; Lin, Yuzhen
ABSTRACT: Based on the rear-step flow reactor, the flashback characteristics of kerosene spray in cross flow under high temperature and high pressure are studied by means of thermocouple and optical test. The research focuses on the process and critical conditions of the spray flashback. The operating conditions are as follows: pressure ranging from 0.25 to 0.75 MPa, temperature ranging from 469 to 800 K, and inlet velocity 40 m/s. The results show that when flashback occurs, the flame is obviously unsteady with strong thermoacoustic oscillation; the starting point of flashback is located at the upper edge of the spray; with the increase of pressure and temperature, the starting point gradually increases in height; the local equivalent ratio of the starting point is about 1; The critical equivalent ratio of flashback increases with the increase of temperature and pressure.